Tracing the Business Success of UD Subur Jaya - Abdul Aziz (Formosa Journal of Sustainable Research, 2023)
Starting a business is one way to achieve economic growth in the community sector. In general, every business tries to be successful in carrying out its operations. The aim of this research is to find out more about the success of UD Subur Jaya's rice milling business. This research is included in qualitative research, which aims to present an overall, factual, and precise picture of the characteristics and characteristics of a particular population or object. Based on the results of research that has been conducted using observation, interview and documentation methods, it is found that the influencing the success of UD Subur Jaya, namely: strategic location selection, quality of products produced, friendly and courteous service, post-sale payments intended for small traders, competitive prices